piR-121380 Is Involved in Cryo-Capacitation and Regulates Post-Thawed Boar Sperm Quality Through Phosphorylation of ERK2 via Targeting PTPN7 - Wang, Yihan; Yuan, Xiang; Ali, Malik Ahsan; Qin, Ziyue; Zhang, Yan; Zeng, Changjun (Frontiers in Cell and Developmental Biology, 2022)
Cryopreservation induces capacitation-like (cryo-capacitation) changes, similar to natural capacitation, and affects the fertility potential of post-thawed sperm. The molecular mechanism of sperm cryo-capacitation during cryopreservation remains unknown. PIWI-interacting RNAs (piRNAs) have been reported to be involved in cryo-capacitation of post-thawed sperm and regulation of sperm motility, capacitation, and chemotaxis. In this study, protein tyrosine phosphatase nonreceptor type 7 (PTPN7) was positively targeted by piR-121380 after a dual luciferase assay. The mRNA expression of PTPN7 and piR-121380 was significantly decreased (P < 0.01), however, PTPN7 protein was significantly increased (P < 0.01) in post-thawed boar sperm. Furthermore, ERK1/2 phosphorylation was reduced during cryopreservation. Six hours after transfection with piR-121380 mimic and inhibitor, the phosphorylation of ERK2 was significantly increased and decreased (P < 0.01), respectively. Furthermore, the highest and lowest total sperm motility, forward motility, and capacitation rate were observed after piR-121380 mimic and inhibitor treatments, respectively. The concentration of intracellular calcium ([Ca2+]i) showed no significant difference after transfection with either piR-121380 mimic or inhibitor at 1, 3 and 6 h. In conclusion, we demonstrated that piR-121380 modulates ERK2 phosphorylation by targeting PTPN7, which induces sperm cryo-capacitation, and eventually affects the motility and fertility potential of post-thawed sperm.